Field evaluation of oxygen consumption by two freshwater decapod morphotypes (Trichodactylidae and Aeglidae); the effect of different times of the day, body weight and sex. Issue 4 (3rd July 2016) - Diawol, V. P.; Torres, M. V.; Collins, P. A.
Abstract: We report an analysis of the effect of two different times of day (noon and dusk), body weight and sex on the oxygen consumption rate (OCR) of the freshwater crabs Trichodactylus kensleyi (Trichodactylidae), Aegla singularis and A. platensis (Aeglidae) in their natural environment. Both families are sympatric in the studied locations, with a co-occurrence found between T. kensleyi and A. singularis or T. kensleyi and A. platensis . The mean OCR was highest in A. singularis and lowest in A. platensis . The OCR was higher in Aegla species at noon, and Trichodactylus consumed more oxygen at dusk. In aeglids, there was no difference in oxygen consumption between noon and dusk. T. kensleyi exhibited statistically significant differences in the OCR between noon and dusk. The oxygen uptake of all three species analysed was not influenced by the sex of the individual but varied according to the animals' weight. The families evaluated share some biological and ecological characteristics, such as diet and habitats, but the strategies used in the regulation of gas exchange at different times of the day were different. Environmental factors may be influencing the oxygen consumption of each morphotype differently.